Characteristics of the prevalence and course of community-acquired pneumonia - Avramenko, Iryna (ScienceRise: Medical Science, 2017)
Aim. To reveal gender-age features, season prevalence, specificity of prevalence and course of severe community acquired pneumonia to raise the effectiveness of the course prognostication, improvement of the diagnostics of patients with community acquired pneumonia of severe course by optimization of the assessment of the clinical-functional state of patients. Materials and methods. For attaining the set aim there were examined 88 patients with the diagnosis “severe community acquired pneumonia”, who underwent the treatment at 3 clinical departments of Dnipro city: MI “Dniprovetrovsk municipal clinical hospital № 2, DRC”, MI “Dniprovetrovsk municipal clinical hospital № 6,DRC” MI “Dniprovetrovsk municipal clinical hospital № 16, DRC” that are the clinical bases of SI “Dnipropetrovsk medical academy, MHP of Ukraine”. Patients were divided in 2 groups depending on the clinical group of pneumonia and also on gender sign. All patients underwent the assessment of the clinical-functional status, careful collection of the anamnesis, clinical-laboratory examinations. Results. In the result of research were received reliable data about differences of features of season prevalence of morbidity, dependence of disease course severity on age and sex, risk factors of severe course of community acquired pneumonia were formed. Conclusions. Severe community acquired pneumonia has its season prevalence that differs from the known epidemic periods. SCAP is more hard in men, especially of elder age group that led to the more frequent necessity of hospitalization of such patients in IC